Leu-enkephalin purification from E. coli cells carrying the plasmid with fused synthetic leu-enkephalin gene - Shemyakin, M.F. (1980)
Chemically synthesized leu-enkephalin gene was fused to a large Eco RI-Bam HI fragment of pBR322 along with a Eco RI fragment of Ch4A phage DNA carrying the promoter and most of the E.coli β-galactosidase gene. The resulting recombinant DNA was used to transform E. coli cells. Transformants were screened for Tc-sensitivity, Am-resistance, and β-galactosidase constitutional synthesis. Restriction endonuclease analysis combined with DNA sequencing of the plasmid DNAs revealed a complete nucleotide leu-enkephalin sequence and Eco RI lac-operon fragment in two possible orientations. Radioimmunoassay for leu-enkephalin activity in BrCN-treated bacterial extracts showed that in vivo leu-enkephalin is synthesized only in strains carrying plasmids with the proper lac-fragment orientation. About 5·10(4) molecules of the former are synthesized per single E. coli cell. One of the clones was used for leu-enkephalin purification. Using 100 g of cells it is possible to obtain about 2 mg of practically pure leu-enkephalin.